Not my father's son ebook A memoir. - Cumming, Alan (2014)
"Equal parts memoir, whodunit, and manual for living . . . a beautifully written, honest look at the forces of blood and bone that make us who we are, and how we make ourselves." —Neil Gaiman In his unique and engaging voice, the acclaimed actor of stage and screen shares the emotional story of his complicated relationship with his father and the deeply buried family secrets that shaped his life and career. A beloved star of stage, television, and film—"one of the most fun people in show business" (Time magazine)—Alan Cumming is a successful artist whose diversity and fearlessness is unparalleled. His success masks a painful childhood growing up under the heavy rule of an emotionally and physically abusive father—a relationship that tormented him long into adulthood. When television producers in the UK approached him to appear on a popular celebrity genealogy show in 2010, Alan enthusiastically agreed. He hoped the show would solve a family mystery involving his maternal grandfather, a celebrated WWII hero who disappeared in the Far East. But as the truth of his family ancestors revealed itself, Alan learned far more than he bargained for about himself, his past, and his own father. With ribald humor, wit, and incredible insight, Alan seamlessly moves back and forth in time, integrating stories from his childhood in Scotland and his experiences today as a film, television, and theater star. At times suspenseful, deeply moving, and wickedly funny, Not My Father's Son will make readers laugh even as it breaks their hearts.